Hydrologic impacts of changing land use and climate in the Veneto lowlands of Italy. (June 2018) - Pijl, Anton; Brauer, Claudia C.; Sofia, Giulia; Teuling, Adriaan J.; Tarolli, Paolo
Abstract: The Po valley in northern Italy is one of Europe's largest and most anthropogenically-modified lowland areas, where intensifying climate and land transformation are increasingly causing water management problems. In this study, the Wageningen Lowland Runoff Simulator (WALRUS) is calibrated, validated, and applied to a reclaimed basin in the Veneto region (Italy) in order to assess the hydrologic impacts of land use and climate change scenarios. First-time model calibration for Mediterranean lowlands resulted in reasonable performance during the training year (NSE 0.77), but lower validation performance (NSE 0.53), while potential for improved calibration was limited by data availability. Scenario analysis covers the historical and future changes in land cover and climate throughout a century (1951–2060), based on aerial imagery analysis, hydrologic measurements, COSMO-CLM regional climate projections and demographics. WALRUS simulations illustrate how land use transformation (i.e. expanded built-up zones and a diminished drainage network) have a strong potential to increase discharge intensities from the catchment, mostly evident in summer peak flow (past −34%; future +48%). A historical scenario of combined land use and climate shows even stronger deviations from the present (annual discharge −19%; summer peak flow −45%), resulting from an observed increase in rainfall intensity and seasonality over the past 50 years. With drier future climate projections, however, the discharge response is moderate in the combined future scenario. Despite the non-optimal model calibration, the presented work in the Veneto region illustrates the directional impact of processes typical of anthropogenic lowlands. Particularly, the impact of observed land transformation seems to diminish the buffering and storage capacity of the catchment, thereby enhancing the hydrologic risks in modern times.